Screening for Susceptibility-Related Factors and Biomarkers of Xianling Gubao Capsule-Induced Liver Injury - Li, Chun-yu; Niu, Ming; Liu, Ya-lei; Tang, Jin-fa; Chen, Wei; Qian, Geng; Zhang, Ming-yu; Shi, Ya-fei; Lin, Jun-zhi; Li, Xing-jie; Li, Rui-sheng; Xiao, Xiao-he; et al. (Frontiers in Pharmacology, 2020)
Although increasing reports from the literature on herbal-related hepatotoxicity, the identification of susceptibility-related factors and biomarkers remains challenging due to idiosyncratic drug-induced liver injury (IDILI). Xian-Ling-Gu-Bao capsule (XLGB) is a famous traditional Chinese medicine prescription and its reported potential hepatotoxicity has attracted great attention. But the mechanism behind it is difficult to determine. In this paper, we found that XLGB-induced liver injury belongs to IDILI through the analysis of clinical liver injury cases. In toxicological experiment assessment, co-treatment with non-toxic dose of lipopolysaccharide (LPS) and XLGB could cause evident liver injury indicated by the significant elevation of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities, as well as obvious liver histologic damage. Whereas it failed to induce observable liver injury in normal rats, suggesting that mild immune stress may be a susceptibility factor for XLGB-induced idiosyncratic liver injury. Moreover, a small amount of inflammatory cell infiltration was observed in the LPS group by liver histopathological examination. Furthermore, plasma cytokines were determined and 15 cytokines (such as IL-1β, IFNγ, and MIP-2α) were acquired by receiver operating characteristic (ROC) curves analysis. Compared with the normal group, the expression of these 15 cytokines in LPS group was significantly up-regulated. Meanwhile, the metabolomics profile showed that mild immune stress caused metabolic reprogramming, including sphingolipid metabolism, phenylalanine metabolism and glycerophospholipid metabolism. 8 potential biomarkers (such as sphinganine, glycerophosphoethanolamine and phenylalanine) were identified by correlation analysis. Therefore, these results suggested that intracellular metabolism and immune changes induced by mild immune stress may be important susceptibility mechanisms for XLGB IDILI.